Using social media as a platform to publicly disclose HIV status among people living with HIV: Control, identity, informing public dialogue. Issue 6 (12th April 2022) - Philpot, Steven P.; Murphy, Dean; Prestage, Garrett; Wells, Nathanael; On behalf of the RISE Study team,
Abstract: Disclosure of HIV status is usually considered a private encounter involving only a limited number of people at a time. Many people living with HIV are strategic about deciding in what contexts, using which approach, to whom, and to what extent they disclose HIV status. However, social media platforms provide opportunities for people to publicly disclose information about themselves to their networks. Utilising semi‐structured interviews with people recently diagnosed with HIV in Australia, we explore how, why, and using what strategies people living with HIV use social media as a means of publicly disclosing positive HIV status. Participants placed importance on having control of how they framed their life with HIV and adopted strategies to control the audience to whom they disclosed. Public disclosure on social media helped participants come out of the 'sero‐closet', empowered identity affirmation, and enabled them to be voices for other people living with HIV to shift public dialogue. We conclude that public disclosure of a positive HIV status can strip HIV disclosure of being associated with delivering private and unpleasant information, and instead reframe living with HIV from a responsibility to disclose to a right to share.